Detecting man in the middle attack implementing timebased verification method - Topu, Syed Naziur Rahman; Ahmed, Saif (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.